Alterations in peripheral blood lymphocyte cytokine expression in obesity - O'Rourke, R. W.; Kay, T.; Lyle, E. A.; Traxler, S. A.; Deveney, C. W.; Jobe, B. A.; Roberts, C. T.; Marks, D.; Rosenbaum, J. T. (Clinical and experimental immunology, 2006)
Summary Obesity is characterized by alterations in immune and inflammatory function. In order to evaluate the potential role of cytokine expression by peripheral blood mononuclear cells (PBMC) in obesity‐associated inflammation, we studied serum protein levels and mRNA levels in PBMC of interleukin (IL)‐6, IL‐1β, tumour necrosis factor (TNF)‐α and IL‐1Ra in nine lean and 10 obese subjects. Serum IL‐1β was undetectable, IL‐1Ra serum levels were elevated, serum levels of TNF‐α were decreased and serum levels of IL‐6 were similar in obese subjects compared to lean subjects, while transcript levels of IL‐6, IL‐1β and TNF‐α, but not IL‐1Ra, were decreased in PBMC from obese subjects. PBMC from obese subjects did, however, up‐regulate cytokine expression in response to leptin. Thus, obesity‐associated changes in IL‐1Ra serum levels and IL‐6 mRNA levels were not correlated with changes in cognate mRNA and serum levels, respectively, while TNF‐α serum levels and PBMC mRNA levels were both decreased in obese patients. While immune alterations in obesity are manifest in peripheral blood lymphocytes, the general lack of correlation between altered serum levels and altered PBMC gene expression suggests that PBMC may not be the source of aberrant serum cytokine levels in obesity.